Hypothesis-based food, feed, and environmental safety assessment of GM crops: A case study using maize event DP-202216-6. Issue 1 (2nd January 2021) - Anderson, Jennifer A; Herman, Rod A.; Carlson, Anne; Mathesius, Carey; Maxwell, Carl; Mirsky, Henry; Roper, Jason; Smith, Brenda; Walker, Carl; Wu, Jingrui
ABSTRACT: Event DP-2Ø2216-6 (referred to as DP202216 maize) was genetically modified to increase and extend the expression of the introduced zmm28 gene relative to endogenous zmm28 gene expression, resulting in plants with enhanced grain yield potential. The zmm28 gene expresses the ZMM28 protein, a MADS-box transcription factor. The safety assessment of DP202216 maize included an assessment of the potential hazard of the ZMM28 protein, as well as an assessment of potential unintended effects of the genetic insertion on agronomics, composition, and nutrition. The history of safe use (HOSU) of the ZMM28 protein was evaluated and a bioinformatics approach was used to compare the deduced amino acid sequence of the ZMM28 protein to databases of known allergens and toxins. Based on HOSU and the bioinformatics assessment, the ZMM28 protein was determined to be unlikely to be either allergenic or toxic to humans. The composition of DP202216 maize forage and grain was comparable to non-modified forage and grain, with no unintended effects on nutrition or food and feed safety. Additionally, feeding studies with broiler chickens and rats demonstrated a low likelihood of unintentional alterations in nutrition and low potential for adverse effects. Furthermore, the agronomics observed for DP202216 maize and non-modified maize were comparable, indicating that the likelihood of increased weediness or invasiveness of DP202216 maize in the environment is low. This comprehensive review serves as a reference for regulatory agencies and decision-makers in countries where authorization of DP202216 maize will be pursued, and for others interested in food, feed, and environmental safety.